Interaction university and school - Gionara Tauchen; Catia Piccolo Viero Devechi (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
Considering that the interaction between universities and middle schools is fundamental for organization and the qualification of the education system, we conducted a qualitative study on twenty public municipal schools of Rio Grande, RS, designed to investigate and understand the effectiveness of university activities (teaching, research and extension) in regard to the promotion and strengthening of the interactions between these institutions. We highlight the activities related to Pibid, the Education Observatory, extension, supervised internships, and to undergraduate and postgraduate research. From comprehensions about these activities, we discuss the interaction between school and university.